The effect of the use of information and communication technology (ICT) learning media on the student’s learning activity in class V SD Negeri Pannara Makassar City - Hamzah, Rahma Ashari (JURNAL PENDIDIKAN DASAR NUSANTARA, 2022)
This study uses a quantitative approach with the type of research True-Experimental Design with Pretest-Posttest Control Group Design. The purpose of this study was to determine the effect and description of student learning activity before and after the use of information and communication technology (ICT) learning media in Pannara Makassar Elementary School. Data collection techniques used observation sheets (observations), questionnaires (questionnaires), and documentation. The population is all fifth grade students of SD Negeri Pannara Makassar. The sampling technique used is the total sampling technique. The data analysis technique used is descriptive analysis and inferential analysis. The results showed that the use of Information and Communication Technology (ICT) learning media was well implemented. Based on the results and implementation. Student learning activity in learning before using Information and Communication Technology (ICT) learning media (freetest) in the experimental group in the low category 24.00%, the medium category 20.00%, the high category 56.00% and in the very high category 24.00% and the control group in the low category was 32.00%, the medium category was 40.00%, the high category was 28.00%, and the very high category was 24.00%. After being treated with the use of Information and Communication Technology (ICT) learning media, there was an increase in student learning activity in the experimental group with low 0.00%, medium 12.00%, high 32.00%, and very high 56.00% categories. While the control group is in the low category of 0.00%, moderate 20.00%, high 56.00%, and very high 24.00%. From these acquisitions, the use of Information and Communication Technology (ICT) learning media has an effect on the learning activities of Pannara Makassar Elementary School students.